Cancer risk associated with the use of valsartan in Korea: A nationwide cohort study. (October 2022) - Jeon, Ha-Lim; Lee, Seon Hee; Nam, Jin Hyun; Shin, Ju-Young
Abstract: Background: Despite valsartan's widespread use, few studies have explored its potential carcinogenicity. We evaluated the association between valsartan and cancer. Methods: We conducted a retrospective cohort study using data from 2002 to 2015 gathered from the National Health Insurance database. Patients with hypertension aged ≥ 30 who used valsartan or other angiotensin II receptor blockers (ARBs) were included. Eligible patients were those with no prior history of the use of any ARBs, diagnosis of cancer, or organ transplantation in the 4 years predating their first use of the drugs of interest. The primary and secondary outcomes included the occurrence of all cancers and site-specific solid cancers, respectively. After applying propensity score (PS) matching, Cox regression was used to calculate the hazard ratios (HRs) and 95 % confidence intervals (CIs). Results: A total of 1, 550, 734 individuals were identified as new users of valsartan or other ARBs. Of the 153, 047 valsartan users, 16, 047 were diagnosed with cancer. No increased risk of overall cancer was observed in valsartan users as compared to other ARB users (aHR = 1.00; 95 % CI, 0.98–1.02). Valsartan was, however, associated with a slightly elevated risk of liver (aHR = 1.09; 95 % CI, 1.01–1.16) and kidney cancer (aHR = 1.11; 95 % CI, 1.02–1.22). Conclusion: Compared with other ARBs, valsartan did not increase the risk of overall cancer. A slightly increased risk for some solid cancers was associated with valsartan use, though the absolute rate difference was small. Highlights: Valsartan did not increase the risk of cancer compared with other ARBs. Valsartan increased the risk of some cancers, but the absolute rate difference was small. No increased risk of cancer was found with increasing duration or cumulative dose.